BENDING VIBRATION CHARACTERISTICS ANALYSIS OF THE CONVEYOR BELT WITH THE STEEL ROPE CORE BASED ON THE ORTHOGONAL ANISOTROPY SHEET MODEL - CHEN HongYue; LI EnDong; ZHANG Kun; MAO Jun; BAI YangXi; MA Ying (Jixie qiangdu)
The transverse free vibration model of the rubber conveyor belt with the steel rope core is established based the small deflection theory of the orthogonal anisotropy sheet model. By using the classical solution method, the analytical solutions of the SFSF boundary model of the lower branch conveyor belt, the SCSC boundary model of the upper branch slot shape bottom, and the SFSC boundary model of the side. The main stiffness of the conveyor belt with the steel rope core is derived by using the Khobar approximation. The previous-order natural frequencies of the lower branch conveyor belt and the upper branch conveyor belt, the vibration type and the variation law of natural frequency with the tension variation are obtained by employing the numerical analysis. The results show that the natural frequencies of the lower and the upper branch of the conveyor belt increase with the increasement of the belt tension, and the tension influences the frequency of the lower branch conveyor belt greatest and the frequency of the upper branch conveyor belt bottom smaller. The researching results provide the bending vibration response analysis and the resonance avoiding design of the conveyor belt with the basis.